The saltmarsh vegetation of the lower Berg River - M. O'Callaghan (Bothalia: African Biodiversity & Conservation, 1994)
The lower Berg River supports approximately 250 ha of estuarine saltmarsh vegetation. Species distribution patterns, as sampled along six transects, are described. Elevation above mean sea level (MSL) is proposed as a strong determinant of these patterns. However, there are no typical patterns. The patchy and irregular distribution patterns possibly result from an inconsistent relationship between species distribution and salinity, tidal inundation and/or competitive interactions.